Who’s your daddy? On the identity and distribution of the paternal hybrid ancestor of the parthenogenetic gecko Lepidodactylus lugubris (Reptilia: Squamata: Gekkonidae) - Karin, Benjamin R.; Oliver, Paul M.; Stubbs, Alexander L.; Arifin, Umilaela; Iskandar, Djoko T.; Arida, Evy; Oong, Zheng; Mcguire, Jimmy A.; Kraus, Fred; Fujita, Matthew K.; Ineich, Ivan; Ota, Hidetoshi; et al. (Zootaxa, 2021)
The widespread parthenogenetic gecko Lepidodactylus lugubris is comprised of several clonal lineages, at least one of which has been known for some time to have originated from hybridization between its maternal ancestor, Lepidodactylus moestus, and a putatively undescribed paternal ancestor previously known only from remote islands in the Central Pacific. By integrating new genetic sequences from multiple studies on Lepidodactylus and incorporating new genetic sequences from previously sampled populations, we recovered a phylogenetic tree that shows a close genetic similarity between the generally hypothesized paternal hybrid ancestor and a recently described species from Maluku (Indonesia), Lepidodactylus pantai. Our results suggest that the paternal hybrid ancestor of at least one parthenogenetic clone of L. lugubris is conspecific with L. pantai and that the range of this species extends to Palau, the Caroline Islands, the Kei Islands, Wagabu, and potentially other small islands near New Guinea. Deeper genetic structure in the western (Palau, Maluku) versus eastern (eastern Melanesia, Micronesia, Polynesia) part of this species’ range suggests that the western populations likely dispersed via natural colonization, whereas the eastern populations may be the result of human-mediated dispersal. The potential taxonomic affinities and biogeographic history should be confirmed with further morphological and genetic analyses, including research on L. woodfordi from its type locality, which would have nomenclatural priority if found to be conspecific with L. pantai. We recommend referring to the wide-ranging sexual species as Lepidodactylus pantai until such a comparison can be made.